Response surface methodology optimization of polyhydroxyalkanoate by recombinant bacillus megaterium PPSPHAR1/1 strain using fish processing waste production - Huyen, Pham Thanh; Bach Thi Mai Hoa,; Linh, Nguyen Trong; Huyen, La Thi; Da, Nguyen Thi (Vietnam Journal of Science and Technology, 2022)
Polyhydroxyalkanoates (PHAs) are biomaterials that are accumulated intracellularly by bacterial cells in response to nutrient imbalances under environmental stress. Polyhydroxybutyrate (PHB) is a bioplastic that is of interest to research to find an alternative to fossil-derived plastics. The optimal physical and nutritional conditions for PHB production were investigated by varying one variable at a time. To achieve maximum PHA production, the culture conditions for B. megaterium pPSPHAR1/1 were optimized through response surface methodology (RSM). The final optimum fermentation conditions included: 13.34 (g/L) glucose; 7.28 (g/L) Na2HPO4; 4.45 (g/L) K2HPO4; MgSO4 0.2; 2 (g/L) (NH4)2SO4; NH4Fe(III) citrate 0.005 %; acid citric 0.1 %; 2 Ml of trace minerals, 3 (%w/v) fish oil; 1.3 (%v/v) fish extract; inoculum size, 10 % (v/v)and temperature of 37 oC for 72 h. Using the optimal medium, the PHB production of this recombinant strain accumulated a PHB content of about 76.2 % per cell dry weight in a 5 L stirred bioreactor.